Avian influenza annual report 2023 - European Food Safety Authority (EFSA); José Cortiñas Abrahantes; Inma Aznar; Iancu Catalin; Lisa Kohnle; Kenneth Fergus Mulligan; Lina Mur; Anca Stoicescu; Aniek vanHoutum; Gabriele Zancanaro (EFSA Journal)
Abstract All European Union (EU) Member States (MSs), along with Iceland, Norway, Switzerland and the United Kingdom (Northern Ireland), conduct surveillance for avian influenza (AI) in poultry and wild birds. EFSA, upon mandate of the European Commission, compiles and analyses this data in an annual report. This summary highlights findings from the 2023 surveillance activities. In 2023, 31 reporting countries (RCs) visited 21,183 poultry establishments (PEs). Of these, 18,557 underwent serological investigations, 2460 underwent virological investigations and 166 underwent both. Among the 18,723 PEs sampled for serological testing, 29 PEs (0.15%) were seropositive for influenza A(H5/H7) viruses, more in detail: 27 PEs tested positive for A(H5), 1 tested positive for A(H7) and 1 tested positive for both strains. These were found in eight RCs (Bulgaria, Poland, Germany, Spain, Sweden, Norway, Iceland and Finland). Of the 2626 PEs sampled for virological testing, 180 PEs (6.85%) were positive for influenza A(H5/H7) viruses. More precisely, 178 tested positive for A(H5), of which 161 positive for HPAI (H5N1) and 2 tested positive for A(H7). Positive PEs were reported by 12 RCs covering 14 different poultry categories. A total of 51,411 wild birds were sampled, with 6717 (13.07%) testing positive for HPAIVs by PCR from 25 RCs. Subtype A(H5N1) was the main influenza A virus identified (6531; 97%), similar to 2022. Twenty RCs reported 1940 wild birds testing positive for LPAI or AIV of unknown pathogenicity. For these, 1372 (67.5%) were nor A(H5) or A(H7), while 568 (29.3%) tested positive for A(H5). These findings reflect the ongoing efforts in early detection and monitoring of avian influenza to mitigate the risk of outbreaks in poultry populations throughout Europe.